PEMBINAAN MASYARAKAT PADA PEREMPUAN TULANG PUNGGUNG KELUARGA DENGAN STRATEGI KOPING MEKANISME DALAM UPAYA PENINGKATAN RESILIENSI - Wahidah, Evita Yuliatul (Community Development: Jurnal Pengembangan Masyarakat Islam, 2019)
AbstractCommunity Service is a medium to bridge the world of education with the community, where universities are faced with the problem of how citizens can face challenges further ahead in the era of globalization. To develop community service activities in a more productive, more structured manner and with more optimal results, there is guidance for women in the family backbone in Bojonegoro. This guidance is by implementing a coping mechanism program to increase resilience.This coaching is designed on the basis of prior research on the correlation of coping mechanism mechanism for resilience in women backbone families with motivation training, self management material and using several methods, including: classical methods with lecture delivery theory in consultation, variations in discussion in space (in door), game method and simulation (out door), and out bond. This guidance is supported by infrastructure facilities including classrooms, LCD projectors, laptops, equipment and supplies for games and simulations and out bonds. Empirically practical, fostering the backbone of women with the coping strategy of this mechanism has a significant impact on increasing resilience.Keywords:     : Community Development, Women's Family Backbone, Coping Strategy Mechanism and Resilience.